2020
DOI: 10.1017/s0033291720004584
|View full text |Cite
|
Sign up to set email alerts
|

Changes in telepsychiatry regulations during the COVID-19 pandemic: 17 countries and regions' approaches to an evolving healthcare landscape

Abstract: in 4 regions, and consequently, in 15 regions telepsychiatry services were reimbursed at the same rate (or higher) than in-person consultations during the COVID-19 pandemic. Conclusions Our results confirm that, due to COVID-19, the majority of countries surveyed are altering telemedicine regulations that had previously restricted the spread of telemedicine. These findings provide information that could guide future policy and regulatory decisions, that facilitate greater scale and spread of telepsychiatry glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
84
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 27 publications
0
84
0
2
Order By: Relevance
“…Furthermore, positive attitudes toward the use of mHealth apps to help alleviate the psychosocial consequences of the pandemic were highly prevalent and associated with an objective need (e.g., more severe levels of psychological distress and higher levels of worrying). There have been also other studies which have reported that individuals have a positive attitude toward, and increasingly use, digital interventions during the current COVID-19 pandemic across the whole spectrum of public mental health provision (i.e., mental health promotion, prevention, and treatment of mental disorders) [36][37][38]49,50], and alterations of telemedicine regulations have been reported [51]. However, mHealth apps provide the opportunity of delivering lowthreshold, personalized mental health care in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, positive attitudes toward the use of mHealth apps to help alleviate the psychosocial consequences of the pandemic were highly prevalent and associated with an objective need (e.g., more severe levels of psychological distress and higher levels of worrying). There have been also other studies which have reported that individuals have a positive attitude toward, and increasingly use, digital interventions during the current COVID-19 pandemic across the whole spectrum of public mental health provision (i.e., mental health promotion, prevention, and treatment of mental disorders) [36][37][38]49,50], and alterations of telemedicine regulations have been reported [51]. However, mHealth apps provide the opportunity of delivering lowthreshold, personalized mental health care in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous barriers to implementing digital clinics have lessened during COVID-19, creating a more hospitable environment in which to establish this new model of care. Significant changes have occurred in the domains of digital health regulation, payment models, and patient and clinician experience with and acceptance of digital tools [ 7 ]. Prior to COVID-19, various regulations around the world limited the scope of practice of digital health.…”
Section: Motivationsmentioning
confidence: 99%
“…In the USA, regulations limiting prescription of controlled substances and the practice of synchronous telehealth across state lines were relaxed, while in countries such as India, national digital health policies were formed for the first time [ 8 ]. Changes in regulation around payment parity for telehealth services were also announced in many countries, making digital care more financially sustainable [ 7 ]. While these regulatory and payment changes are currently temporary, they will likely endure in some fashion.…”
Section: Motivationsmentioning
confidence: 99%
“…Relatedly, patients’ general attitudes could influence their perceptions of the reasons for the deterioration of their mental health and the reported reasons may therefore not necessarily reflect the impact of the lockdown per se. For instance, patients who were generally unsatisfied with their psychiatric treatment may have consciously or subconsciously used the survey as an opportunity to voice this opinion and thus have attributed their perceived deterioration to “poorer access to psychiatric treatment.” However, psychiatric care has objectively changed during the pandemic, 34,39-41 and it is concerning that nearly 43% of the respondents who reported an overall worsening of their mental health during lockdown attributed it, at least in part, to reduced access to treatment. Fifth, the findings of the present study may not generalize to other countries and health care settings.…”
Section: Discussionmentioning
confidence: 99%